2000
DOI: 10.1126/science.288.5469.1257
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Prion Replication in Spleens of Mice Lacking Functional Follicular Dendritic Cells

Abstract: In scrapie-infected mice, prions are found associated with splenic but not circulating B and T lymphocytes and in the stroma, which contains follicular dendritic cells (FDCs). Formation and maintenance of mature FDCs require the presence of B cells expressing membrane-bound lymphotoxin-alpha/beta. Treatment of mice with soluble lymphotoxin-beta receptor results in the disappearance of mature FDCs from the spleen. We show that this treatment abolishes splenic prion accumulation and retards neuroinvasion after i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
234
1
6

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 341 publications
(251 citation statements)
references
References 37 publications
9
234
1
6
Order By: Relevance
“…Complement components C1q and C3 and cellular complement receptors have been shown to play an important role in the localization of scrapie infectivity to FDCs (32,36). Since PrP c expression is also eliminated in lymphoid follicles after treatment with LT␤R-Ig (37,46), these data suggest the capability of FDCs, if present, to acquire and replicate TSE infectivity would be temporarily abolished for at least 28 days. The fate of the FDCs after LT␤R-Ig treatment is not known, but several mechanisms could be responsible either singularly or in combination.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Complement components C1q and C3 and cellular complement receptors have been shown to play an important role in the localization of scrapie infectivity to FDCs (32,36). Since PrP c expression is also eliminated in lymphoid follicles after treatment with LT␤R-Ig (37,46), these data suggest the capability of FDCs, if present, to acquire and replicate TSE infectivity would be temporarily abolished for at least 28 days. The fate of the FDCs after LT␤R-Ig treatment is not known, but several mechanisms could be responsible either singularly or in combination.…”
mentioning
confidence: 76%
“…We and others have previously shown that, in the temporary absence of mature FDCs after treatment with LT␤ receptorimmunoglobulin fusion protein (LT␤R-Ig [16]), early scrapie accumulation in the spleen is blocked and neuroinvasion is significantly delayed (37,46). Since these studies imply that FDCs could be targeted for early therapeutic intervention against TSE agents, further experiments were performed in the current study to address the following questions.…”
mentioning
confidence: 99%
“…Scrapie infection (Montrasio et al, 2000) Viral shock LCMV infection (Puglielli et al, 1999) LT signaling in autoimmune disease Supplementary Information accompanies the paper on the Oncogene website (http://www.nature.com/onc)…”
Section: Lt Signaling In Infectious Diseasesmentioning
confidence: 99%
“…Dans la pulpe blanche et la pulpe rouge on peut observer des fibres à cholécystokinine-8 3 . Enfin, le long de fins vaisseaux dans la pulpe blanche on trouve des fibres à neurotensine 4 . Aucune structure nerveuse cholinergique n'a été mise en évidence dans la rate [9].…”
Section: Revuesunclassified
“…La maturation des FDC est un point crucial dans le phénomène de lymphoinvasion et elle requiert la présence de lymphocytes B, porteurs de lymphotoxine /. Une déficience en FDC matures réduit significativement la susceptibilité de l'hôte pour l'agent, la lympho-invasion est interrompue et la neuro-invasion retardée [4].…”
unclassified